Evaluation of Corporate Social Responsibility programs for local communities around mining companies in Kalimantan, Indonesia: environmental, economic, and social perspectives - Akhmad Zamroni; Wahyu Endah Christiani Putri; Saurina Tua Sagala (Sustinere: Journal of Environment and Sustainability, 2022)
The purpose of this study is to evaluate Corporate Social Responsibility (CSR) programs for local communities around mining companies in Kalimantan, Indonesia, based on environmental, economic, and social perspectives. We create evaluation criteria consisting of; six on the environmental perspective, three on the economic perspective, and two on the social perspective. CSR reports are collected from the company website. Each company was given a score based on whether these evaluation criteria were present (1) or absent (0). The evaluation scores of the CSR mining companies programs’ in Kalimantan, Indonesia are high in considering cleaner production, waste reduction, material flow management, and recycling, committed to managing energy and water, developing infrastructures surrounding mining companies, has good corporate ethics, and encourages employees to volunteer for social causes and provides incentives for these activities; medium in committed to following all applicable laws and policies concerning environmental standards and policies, committed to conserving biodiversity, committed to managing sound and vibration from mining activities as well as protecting the air quality around the mining area, and enhancing self-employment options for local communities; low in taking long-term factors into accounts, such as global climate change and other environmental threats, and providing jobs opportunities for local communities. From the evaluations above, access to information, public participation, and transparency in discussing areas of corporate-community issues are all things that mining companies must improve. If there is a lack of congruence between aim, activity, and effect, civil society organizations should frequently criticize mining companies' CSR operations.